“It Doesn’t Really Show.” : The Invisibility of Diversity, Equity, and Inclusion in B2B Sales - Piekkari, Johanna (My University, 2024)
The purpose of this thesis was to investigate the relevance of Diversity, Equity, and Inclusion (DEI) initiatives in a business-to-business (B2B) sales context. The thesis addressed the following research questions: (1) How has corporate social responsibility (CSR) gained prominence in B2B sales? (2) What diversity, equity and inclusion (DEI) initiatives are currently undertaken by organizations? and (3) What is the relevance of organizations’ DEI initiatives to a B2B purchaser? This thesis integrates DEI into the study of B2B sales and in doing so, it contributes to previous research in both marketing and DEI. DEI research has mainly focused on intra-organizational relationships in terms of e.g., organizational and team performance, with only a handful of studies examining DEI in marketing. However, to the best of this researcher’s knowledge, the present thesis is one of the first studies on DEI in B2B sales. This is a novel and emerging field of research which is only starting to gain scholarly attention. The study was conducted as a case study by interviewing six B2B purchasers of a case organization operating on the energy sector. The findings of the study revealed that B2B customers are increasingly aware of responsible practices and demand it from their suppliers. Pre-questions asked before the request for proposals concern, for example, certificates, commitment to code of conduct, fulfilment of sustainability criteria, compliance with EU regulations and law, as well as concrete actions to achieve science-based targets. The interview data suggested that these were typical topics discussed in today’s B2B sales. Thus, CSR has definitely gained prominence in B2B sales, both in selling and purchasing. Before the COVID-19 pandemic, global organizations made vocal commitments to DEI in order to respond to the intense public discussion. Recently, however, labour and economic challenges have shifted the focus away from DEI. This shift may have stemmed from the perception that DEI is not as critical to business success as other factors. Few organizations have adopted a strategic approach to DEI work with a DEI program. The lack of a strategic approach may explain why organizations do not communicate their approach towards DEI to external stakeholders, such as customers. Based on this study, DEI has gained limited visibility and prominence in sales. When selecting a supplier in the energy sector, which is the specific industry context of this thesis, B2B purchasers still prioritize price, quality, and timeliness. However, information of DEI is considered valuable among B2B customers. As DEI is a part of CSR, providing comprehensive CSR information fosters trust and assures customers that they can be confident about their collaboration partners. Expectations towards large firms as exemplary organizations for, others to follow, were also expressed in the interviews. The findings suggest that B2B purchasers consider social responsibility as an emerging field that will become more important in the next few years. However, there is still room for pioneering action in this area, and the B2B purchasers would like to see larger organizations occupy this space showing good example to others in this industry.

Tämän tutkielman tarkoituksena oli tutkia monimuotoisuuden, yhdenvertaisuuden ja osallisuuden (DEI) merkitystä yritysten välisessä (B2B) myynnissä. Työssä vastattiin seuraaviin tutkimuskysymyksiin: (1) Miten yritysvastuun (CSR) merkitys on kasvanut B2B-myynnissä? (2) Millaisia tekoja monimuotoisuuden, yhdenvertaisuuden ja osallisuuden (DEI) edistämiseksi organisaatiot tällä hetkellä tekevät? ja (3) Millainen merkitys organisaatioiden DEI-teoilla on B2B-ostajalle? Tutkielma integroi DEI:n osaksi B2B-myyntiä ja tuo siten lisäarvoa aikaisempaan tutkimukseen niin markkinoinnin kuin DEI:n osalta. Aikaisemmat tutkimukset DEI-työhön liittyen ovat pääasiassa keskittyneet organisaatioiden sisäisiin suhteisiin, kuten tiimien suorituskykyyn, ja vain muutama tutkimus on tarkastellut DEI-työtä markkinoinnin näkökulmasta. Tämän tiedon valossa, kyseinen tutkielma on yksi ensimmäisistä tutkimuksista DEI:stä B2B-myynnissä. Aihealue on uusi ja nouseva tutkimusala, joka vasta alkaa saamaan akateemista näkyvyyttä. Tämä tutkielma toteutettiin tapaustutkimuksena haastattelemalla kuutta B2B-ostajaa tapausorganisaatiosta, joka toimii energia-alalla. Tutkimuksen tulokset osoittivat, että B2B-asiakkaat ovat yhä enemmän tietoisia vastuullisista käytännöistä ja vaativat niitä toimittajiltaan. Ennen tarjouspyyntöä esitetään esikysymyksiä, jotka koskevat esimerkiksi sertifikaatteja, sitoutumista toimittajien toimintaperiaatteisiin (eng. supplier code of conduct), vastuullisuuskriteerien täyttämistä, EU:n asetusten ja lakien noudattamista sekä konkreettisia toimia tieteeseen perustuvien tavoitteiden saavuttamiseksi. Haastatteluaineiston perusteella nämä olivat tyypillisiä aiheita B2B-myynnissä tänä päivänä. Näin ollen yritysvastuu on ehdottomasti tullut osaksi niin B2B-myyntiä kuin -ostamista. Ennen COVID-19-pandemiaa globaalit organisaatiot tekivät suuria sitoumuksia DEI-työn suhteen vastatakseen intensiiviseen julkiseen keskusteluun. Viime aikoina kuitenkin työvoima- ja taloudelliset haasteet ovat siirtäneet huomion pois DEI-työstä. Tämä on saattanut johtaa siihen, ettei DEI-työtä, ettei DEI-työtä nähdä yhtä kriittisenä liiketoiminnan menestyksen kannalta kuin muita tekijöitä. Vain harvat organisaatiot ovat ottaneet strategisen lähestymistavan DEI-työhön. Strategisen lähestymistavan puute saattaa selittää, miksi organisaatiot eivät viesti lähestymistavastaan DEI-työhön ulkoisille sidosryhmille, kuten asiakkaille. Tämän tutkimuksen perusteella DEI on saanut rajallista näkyvyyttä B2B-myynnissä. Kun valitaan toimittajaa energia-alalla, joka on tämän tutkielman toimialaympäristö, B2B-ostajat asettavat edelleen etusijalle hinnan, laadun ja toimitusajan. Kuitenkin tieto toimittajan DEI-käytännöistä katsotaan olevan arvokasta B2B-asiakkaille. Koska DEI-työ on osa sosiaalista vastuuta ja siten myös osa yritysvastuuta, kattavan vastuullisuustiedon tarjoaminen luo luottamusta ja varmistaa asiakkaille, että he voivat luottaa yhteistyökumppaneihinsa. Tutkielman tulokset viittaavat siihen, että B2B-ostajat pitävät sosiaalista vastuuta nousevana alana, joka tulee tulevina vuosina yhä tärkeämmäksi. Tällä alalla on vielä tilaa edelläkävijätoimille, ja B2B-ostajat haluaisivat nähdä suurempien organisaatioiden ottavan tämän tilan haltuun ja näyttävän hyvää esimerkkiä muille tässä teollisuudessa.
Keywords: diversity, equity, inclusion, DEI, B2B sales, B2B purchasing, monimuotoisuus, diversiteetti, yhdenvertaisuus, osallisuus, yhteisöllisyys, inklusiivisuus, B2B-myynti, B2B-hankinta